Ki-67 as a Prognostic Marker in Squamous Cell Carcinomas of the Vulva: A Systematic Review - Klamminger, Gilbert Georg; Eltze, Elke; Bitterlich, Annick; Degirmenci, Yaman; Hasenburg, Annette; Wagner, Mathias; Nigdelis, Meletios P. (Journal of clinical medicine, 2025)
Background/Objectives: To evaluate the prognostic impact of immunohistochemical ki-67 staining analysis regarding lymph node involvement and survival data (overall/progression-free survival) in squamous cell carcinoma of the vulva. Methods: A systematic literature search of English and German articles was conducted (PubMed, Embase, Scopus, Web of Science) from 1980 to December 2023, including the search terms “vulvar Neoplasms”, “vulvar cancer”, “vulvar carcinoma”, “vulvar tumor”, ”vulvar tumour”, “vulvar malignancy”, “vulvar malignant”, “ki-67”, “MIB-1”, “MIB1”, “proliferative index”, “proliferative activity”, “mitotic index”, and “mitotic count”. Study quality was assessed using a two-step “mixed-criteria” approach; to synthesize study results, a narrative summary is provided. Results: In total, 13 studies were included in this systematic literature review. In general, two distinct methods of staining interpretation could be retrieved: A “pattern-based” method, as well as a cell count-based method. Ten of the included studies examined the relationship between ki-67 and lymph node involvement, nine studies included survival data as a parameter of interest; and only five studies defined both groin lymph node metastasis and survival data as outcome variables. While nine out of ten studies found no statistically significant association between ki-67 staining and lymph node metastasis, five out of nine studies determined an association between ki-67 status and overall survival, especially when employing a “pattern-based” method of staining interpretation. Conclusions: The prognostic value of ki-67 staining in terms of survival data has been reported ambivalently and should be subject to future studies. Furthermore, we did not find convincing evidence of an association between ki-67 and lymph node involvement.